Literary Tourism: Maintaining Balinese Identity in 'Host-Guest' Interaction in Short Stories by Balinese Writers - Sutanegara Pidada Ida Bagus Jelantik; I Nyoman Darma Putra (Institut Seni Indonesia Denpasar, 2023)
The development of tourism in Bali with strong socio-cultural influences has inspired Balinese writers to create literary works about the interaction between Balinese peopleÂ (hosts) and tourists (guests), both in Indonesian and Balinese language. This study examines how Balinese authors maintain Balinese identity in host-guest interactionsÂ featured in short stories by Balinese writers. The main object of research is the anthology of Balinese short stories Mekel Paris (Madame Paris, 2012) by IBW Keniten because all short stories in this anthology contain stories of interactions between Balinese and foreigners. Data from the short stories and interviews with authors were analyzed qualitatively using a tourism literary approach, an approach that uses anthropological tourism theory of host-guest contactÂ introduced by Valene Smith. The results showed that there are various forms of host-guest interaction expressed in the Mekel Paris anthology, namely harmonious, conflict, mutualistic, and transactional interactions. Although there are various forms of interaction, all of them have one goal, which is to convey the message so that the Balinese people are not carried away by foreign influences, but are firm in maintaining Balinese identity. In addition to enriching the discussion on how Balinese people maintain their identity, this article also contributes to the development of the study of tourism literature that is growing rapidly in Indonesia.